Identification and Characterization of EvpQ, a Novel T6SS Effector Encoded on a Mobile Genetic Element in Edwardsiella piscicida - Li, Duan You; Liu, Ying Li; Liao, Xiao Jian; He, Tian Tian; Sun, Shan Shan; Nie, Pin; Xie, Hai Xia (Frontiers in Microbiology, 2021)
In this study, a hypothetical protein (ORF02740) secreted by Edwardsiella piscicida was identified. We renamed the ORF02740 protein as EvpQ, which is encoded by a mobile genetic element (MGE) in E. piscicida genome. The evpQ gene is spaced by 513 genes from type VI secretion system (T6SS) gene cluster. Low GC content, three tRNA, and three transposase genes nearby evpQ define this MGE that evpQ localizes as a genomic island. Sequence analysis reveals that EvpQ shares a conserved domain of C70 family cysteine protease and shares 23.91% identity with T3SS effector AvrRpt2 of phytopathogenic Erwinia amylovora. Instead, EvpQ of E. piscicida is proved to be secreted at a T6SS-dependent manner, and it can be translocated into host cells. EvpQ is thereof a novel T6SS effector. Significantly decreased competitive index of ΔevpQ strain in blue gourami fish (0.53 ± 0.27 in head kidney and 0.44 ± 0.19 in spleen) indicates that EvpQ contributes to the pathogenesis of E. piscicida. At 8-, 18-, and 24-h post-subculture into DMEM, the transcription of evpQ was found to be negatively regulated by Fur and positively regulated by EsrC, and the steady-state protein levels of EvpQ are negatively controlled by RpoS. Our study lays a foundation for further understanding the pathogenic role of T6SS in edwardsiellosis.